América Latina e Caribe, crise, emergências e solidariedade. Um olhar da geopolítica do vírus SARS-CoV-2 - Delgado Estrada, Juan Manuel (2020)
This 2020 will be the year that the world ceased to be as it was known, since many flaws and failures of the world-system were hidden, where the meta story that we were on the right path to the development model imposed by the global elites. Problems such as climate change and hunger were denied, and the economy was prioritized over health, education, and security. The arrival of the SARS -Cov-2 virus pandemic to our continent confirmed the fragility in providing essential services such as health from a state dismantled in the 80’s and 90’s by the directives of the Washington consensus and the organizations multilateral financial institutions such as the IMF and the World Bank. The coloniality of Power has been evidenced in short-term public policies and not from a geopolitical vision with a horizon from the governance and governability of national and sub-national territories. The actions of the Latin American and Caribbean elites imposing the short-term economy against health during the pandemic of the SARS-CoV-2 virus has not had ideologies nor who was the worst or best from the right or the left, profit was imposed against generosity and work in common, but also citizenship has been organized from below and in solidarity and reciprocity as the original peoples did well with good living or living well. Only by controlling the SARS –Cov-2 virus pandemic can the economic reactivation be started, there is no alternative but to put health and life above economy and profit.